A PROPOSED SERVICE PORTAL PLATFORM FOR APPLIANCE MAINTENANCE IN BANGKOK - Suwanpanmanee, Hao Hao; Shinasharkey, Taminee; Unyapoth, Asis (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2022)
Nowadays, handheld device is the tool people carry all along their daily life for both personal and business purpose especially for service and shopping proposes. Currently, there are already existing several famous portals for shopping goods for example Shopee, Lazada, and Central. However, the services such as maintenance service, are still seen either limited to physical barrier in the local area or sitting in the unadvertised domain name unless visited physically. This paper presents a proposed service platform for maintenance daily life appliance usage which scattered across cities by initiate a portal application. Looking at many famous applications to utilize as customer service platform, LINE application was chosen as launching service channel. The application provides the functions that allows customer who bring their appliance to drop at the specific locations and customers to bring in their shoes, choose the service type and make payment, and pick up later when notified as finished. Whilst back office is located locally, the orders coming in and out can be picked up by scheduled transport without the need to consume expensive space. The trial location is established. By integrating maintenance service over IT, local maintenance service like shoes fixing can obtain more traffic and deliver more value. Each pair of shoes are separated by order which can be tracked for individual. Both cobblers and customers can communicate via LINE to eliminate any confusions and mistakes. This brings more transparency, reliability, and trust to the customers.